Enhancement of Curcuma Longa and Zingiber Officinale Bioactives Extraction through High-Pressure Processing (HPP) Method for Functional Food and Beverages - Halim, Noor Syamimi; Mohd Kassim, Angzzass Sari (Progress in Engineering Application and Technology, 2023)
Surveys indicated food and beverages enhanced with bioactive compounds from natural plants (functional foods and beverages) have huge advantages on human health and promote a good state of mental and physical well-being. However, extraction of the bioactive compounds pose several challenges such as extreme temperature, long extraction time and toxic solvent used, hence degrading the integrity of the bioactive compounds. The aim of this research is to optimize the operating conditions of a green extraction method using High Pressure Processing (HPP) for the plants of Curcuma Longa and Zingiber Offinale. The operating condition parameters selected are pressure (200 MPa, 600 MPa), extraction time (5, 10, 15 mins) and solid-to-liquid ratio (1:15, 1:7, 1:4.3 % w/w). The nutritional analysis was conducted for total phenolic content (TPC) and the functional activities analyzed were total anti-oxidant (TAO) and total anti-inflammatory (TAI). The findings indicate, for C. Longa, the optimum HPP operating conditions for maximum TPC (8.033 ug/ml) and maximum TAO (1.432 mg/ml) are 600 MPa, 10 min extraction time and 1:43% w/w solid:liquid ratio. However, if turmeric TAI (94.1%) is targeted, the best HPP operating conditions are 200 MPa, 10 min extraction time and 1:15% w/w solid:liquid ratio. Meanwhile, for Z. Officinale, 200 MPa seems to be the best operating pressure to retain the highest nutritional content and functional activities. However, depending on the targeted content or activity, the best extraction time varies from 5 min to 15 min and the best solid:liquid ratio varies between 1:4.3% to 1:15%. This research demonstrates that an optimized green extraction method suitable for the application of functional food and beverages is possible and could be enhanced for targeted properties of interest, such as anti-oxidant and anti-inflammatory.